2016
DOI: 10.22436/jnsa.009.06.108
|View full text |Cite
|
Sign up to set email alerts
|

On the extended multivalued Geraghty type contractions

Abstract: In this paper we present some absolute retract results for modified Geraghty multivalued type contractions in b-metric space. Our results, generalize several existing results in the corresponding literature. We also present some examples to support the obtained results. c 2016 all rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…2 Department of Mathematics, Çankaya University, 06790, Ankara, Etimesgut, Turkey. 3 Department of Mathematics and General Sciences, Prince Sultan University, P.O. Box 66833, 11586, Riyadh, Saudi Arabia.…”
Section: Fundingmentioning
confidence: 99%
“…2 Department of Mathematics, Çankaya University, 06790, Ankara, Etimesgut, Turkey. 3 Department of Mathematics and General Sciences, Prince Sultan University, P.O. Box 66833, 11586, Riyadh, Saudi Arabia.…”
Section: Fundingmentioning
confidence: 99%
“…This notion became popular and raised interest among researchers after the paper of Huang and X. Zhang [1] in 2007. Since then, a number of authors got the characterization of several known fixed point theorems in the context of Banach-valued metric space, such as, [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Following this success, many authors have continued to work on this trend and reported several improvements, advances in the setting of b-metric spaces, see e.g. [5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%